2007
DOI: 10.1088/0953-4075/40/2/r01
|View full text |Cite
|
Sign up to set email alerts
|

Classical fields approximation for bosons at nonzero temperatures

Abstract: Experiments with Bose-Einstein condensates of dilute atomic gases require temperatures as low as hundreds of nanokelvins but obviously cannot be performed at zero absolute temperature. So the approximate theory of such a gas at nonzero temperatures is needed. In this topical review we describe a classical field approximation which satisfies this need. As modes of light, also modes of atomic field may be treated as classical waves, provided they contain sufficiently many quanta. We present a detailed descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
167
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(167 citation statements)
references
References 87 publications
0
167
0
Order By: Relevance
“…An alternative approach to simulate the dynamics of BECs at finite temperature is the classical field, or c-field methodology [49][50][51]. Intuitively, a classical field treatment of a BEC will be a reasonable approximation when the system has a significant number of modes with large occupation numbers n i = k B T / i 1, where i is the energy of the mode [52].…”
Section: Appendix A: Classical Field Simulationsmentioning
confidence: 99%
“…An alternative approach to simulate the dynamics of BECs at finite temperature is the classical field, or c-field methodology [49][50][51]. Intuitively, a classical field treatment of a BEC will be a reasonable approximation when the system has a significant number of modes with large occupation numbers n i = k B T / i 1, where i is the energy of the mode [52].…”
Section: Appendix A: Classical Field Simulationsmentioning
confidence: 99%
“…1, we can see that the splitting produces excitations which may diminish the condensate fraction. To analyze the condensate fraction, one needs the so-called c-field approach [40][41][42]. Such an analysis is helpful to evaluate the performance of atomic beam splitters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that dark solitons are spontaneously generated in quasi-one-dimensional Bose gases at equilibrium [16]. By analyzing the statistical distributions of excitations within both the Lieb-Liniger model [17] and the classical fields approximation [18,19] we proved that type II excitations are indeed quantum solitons [20].…”
mentioning
confidence: 90%
“…Each classical field belonging to the canonical ensemble obeys the following equation of motion [19]:…”
mentioning
confidence: 99%
See 1 more Smart Citation